Aprendizaje Basado en el Pensamiento para el proceso de enseñanza aprendizaje de la asignatura de Física - Pinzón Jumbo, Manuel Alejandro (2025)
The teaching of Physics presents significant challenges due to its experimental and conceptual nature, so it is opportune to search for effective pedagogical methods that promote a deep and lasting understanding of its concepts, for this it is necessary to optimize the Teaching-Learning Process in the educational act. In this way, Thinking-Based Learning is an alternative pedagogical approach that aims to develop effective thinking in students, in this sense, this research seeks to analyze Thinking-Based Learning in the development of the TeachingLearning Process of the subject of Physics, for this, within the methodological framework a qualitative approach was taken and the type of research was descriptive, using the collection of information as a technique and the content and bibliographic files and the search log as instruments. In addition, a deductive method was followed by making a bibliographic review of all the research found in different web search engines about their background and characteristics, this information was collected in the instruments following inclusion and exclusion criteria, with this it was obtained as results that its implementation in the classroom and, the use of strategies and resources are adequate for the development of the teaching-learning process, concluding that the ThinkingBased Learning allows the development of the Teaching-Learning Process in an assertive way. Furthermore, the strategies and resources used in its application are adequate for the learning of students in Physics. Key words: Teaching Learning, Physics, Thinking-Based Learning, Active Learning